Dielectric performance controlled by magnetic field in PZT-BFO gradient multiferroic ceramics. (4th July 2017) - He, Xiaojun; Liu, Bao; Wang, Yanxu; Pan, Yubai; Lin, Jinrong; Wang, Feifei; Tang, Yanxue; He, Xiyun; Qiu, Pingsun; Sun, Dazhi
ABSTRACT: Gradient ceramics based on (1-x)PZT + xBiFeO3 (x = 0.01, 0.05, 0.10, Zr/Ti = 95/5) were prepared by a conventional solid-state reaction process. The perovskite structure in the system was confirmed by X-ray diffraction while the microstructure of the composites was characterized by scanning electron microscopy. It was observed that gradient ceramics possess both ferroelectric and ferromagnetic properties at room temperature. A large electromagnetic coupling effect was observed in such gradient system as well. It indicates that gradient ceramics with larger component differences may result in bigger dielectric change under magnetic field. Besides, electromagnetic coupling effect is not directly proportional to magnetism. The related mechanism was discussed with respect to diffusion behavior in the graded material.